DESCRIPTIVE ANALYSIS OF CLINICAL AND DEMOGRAPHIC DATA OF SELECTED GROUP OF PATIENTS WITH PULMONARY EMBOLISM - Baloski Marjan; Buklioska Ilievska, Daniela; Hasan Taner; Nedeska Minova Natasa; Prgova-Veljanova Biljana; Nancheva Boguchevska Andrea; Brishkoska-Boshkovski Vesna; Nancheva, Jasminka; Boshevski Marijan; Panov, Saso (Macedonian Association of Anatomists and Morphologists, 2020)
Pulmonary embolism is a relatively common clinical entity accompanied with a high mortality and is a perplexing diagnostic and therapeutic problem. Current research indicates that pulmonary embolism has a multifactorial and complex pathogenesis. Genetic factors have been under extensive research during the past two decades. The aim of this study was to present a descriptive analysis of demographic and clinical data obtained thus far from 31 patients with documented pulmonary embolism. In our patient group, almost half of the patients were non-smokers and all denied alcohol consumption. More than 80% of the patients had no history of previous pulmonary embolism and no thrombophlebitis, but nearly two thirds of all patients had deep vein thrombosis. A history of acute myocardial infarction existed in about 6.5% of patients, as well as ischemic stroke. Arterial hypertension was present in about one-third of patients, dyslipidemia in 42%, and type 2 diabetes in approximately 13%. Only one patient had an anamnestic data for chronic renal disease, while none had a history of hepatic disease. The results of the analysis of demographic-clinical data of patients are concordant with the results of the previously published studies.
Keywords: pulmonary embolism; thromboembolism; gene polymorphism